2016
DOI: 10.18632/oncotarget.9322
|View full text |Cite
|
Sign up to set email alerts
|

Emx2as a novel tool to suppress glioblastoma

Abstract: Glioblastoma is a devastating CNS tumour for which no cure is presently available. We wondered if manipulation of Emx2, which normally antagonizes cortico-cerebral astrogenesis by inhibiting proliferation of astrocyte progenitors, may be employed to counteract it. We found that Emx2 overexpression induced the collapse of seven out of seven in vitro tested glioblastoma cell lines. Moreover, it suppressed four out of four of these lines in vivo. As proven by dedicated rescue assays, the antioncogenic activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…These results were confirmed by qRT-PCR, showing increased GFAP mRNA levels in differentiated cells from all the three GBMs as compared to the respective CSCs (Figure 2C ). All GBM CSC cultures used in this study have been evaluated in previous experiments for the ability to form tumors when orthotopically xenotransplanted in the brain of NOD/SCID mice, confirming the retaining of tumorigenic activity even after prolonged in vitro growth (Corsaro et al, 2016 ; Falcone et al, 2016 ).…”
Section: Resultssupporting
confidence: 70%
“…These results were confirmed by qRT-PCR, showing increased GFAP mRNA levels in differentiated cells from all the three GBMs as compared to the respective CSCs (Figure 2C ). All GBM CSC cultures used in this study have been evaluated in previous experiments for the ability to form tumors when orthotopically xenotransplanted in the brain of NOD/SCID mice, confirming the retaining of tumorigenic activity even after prolonged in vitro growth (Corsaro et al, 2016 ; Falcone et al, 2016 ).…”
Section: Resultssupporting
confidence: 70%
“…Indeed, EMX2 has a documented anti-proliferative effect in vitro and anti-tumorigenesis effect in vivo in some solid cancers [ 28 , 45 – 47 ]. In GB cell culture, Falcone et al reported that proliferation inhibition induced by EMX2 was associated with cell collapse and apoptosis activity within 7–8 days [ 31 ]. We did not observe enhanced cell death until 7 days of culture, and we observed no sign of apoptosis over 16 days of culture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, EMX2 expression has documented prognostic and/or predictive values for survival of malignant pleural mesothelioma [ 29 ] and lung adenocarcinoma [ 30 ]. Recently, Falcone et al reported that EMX2 overexpression suppresses GB growth both in vitro and in vivo, and induces apoptosis in GB cells [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emx2 (empty spiracles homeobox 2) is a transcription factor bearing multiple functions in neuron development, progression and survival, its expression was undetectable in GBM patient derived cultures [ 74 ]. Overexpression of Emx2 in U87MG and T98G cell lines and five GBM cultures from patients, in which Emx2 was selectively activated in only the tumor cells without effect the health cells and was TetON controlled by doxycycline, caused the expansion of the cells arrested for proliferation, significant alteration on the expression of genes related with mitogenic and RTK signaling, and the genes controlling early G1 checkpoint in five GBM patient cultures, and caused the cultures collapsed within 7–8 days after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of Emx2 in U87MG and T98G cell lines and five GBM cultures from patients, in which Emx2 was selectively activated in only the tumor cells without effect the health cells and was TetON controlled by doxycycline, caused the expansion of the cells arrested for proliferation, significant alteration on the expression of genes related with mitogenic and RTK signaling, and the genes controlling early G1 checkpoint in five GBM patient cultures, and caused the cultures collapsed within 7–8 days after treatment. By restricting Emx2 overexpression ( Emx2 overexpression is highly toxic to neurons) in the tumor cells in xenograft mice, the antioncogenic activity of Emx2 was evidence [ 74 ].…”
Section: Introductionmentioning
confidence: 99%